PELATIHAN PEMBUKUAN DIGITAL MENGGUNAKAN APLIKASI BUKU WARUNG BAGI UMKM DI DESA KARANGJAYA - Sari, Mayang Permata; Fajarwati, Diana; Supratno, Setyo (Universitas Islam 45 Bekasi, 2023)
The digital bookkeeping training program is an effort to develop businesses to better manage their business finances. Development in a business needs to be done by utilizing technology from traditional to digital methods. This digital bookkeeping training can help MSMEs record their financial books easily using the BukuWarung application. The BukuWarung application can make it easier for MSMEs to carry out bookkeeping and recording of their business finances. Because it contains various features that make business activities easier, can reduce the cost of using paper, the risk of human error and loss of physical evidence because data is stored on a smartphone, and there is financial report analysis. So, business actors no longer need to record manually. The training was carried out with one of the MSMEs in Karangjaya village, namely Kedai Syabil, which is a food shop in Kobakrengas hamlet. This activity produces MSME players who are aware of the importance of financial bookkeeping in a business, and becomes a motivation for business development in carrying out bookkeeping every day in their business.